Personal Branding Influencer Nadia Ninette melalui Konten Olah Raga dan Pola Hidup Sehat di Media Sosial Instagram - Catharine, Femy Maria; Poerana, Ana Fitriana; Rifai, Maulana (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The public gets to know a figure through their work and whatever they present. Through personal branding, an influencer can become more recognized by the public, not only by their followers but also by other parties, especially those involved in fields related to the influencer. According to Peter Montoya, there are 8 main concepts in the formation of personal branding: specialization, leadership, personality, distinctiveness, visibility, unity, persistence and goodwill. In this research, the focus is only on 6 concepts, excluding distinctiveness and unity. This study aims to understand how Nadia Ninette, as an influencer and content creator, fulfills 6 out of 8 personal branding concepts on the Instagram social media platform through sports and healthy lifestyle content. This research uses a descriptive qualitative method through interviews, observations, and documentation. The objects to be examined are various sports and healthy lifestyle content by Nadia Ninette on Instagram, including diet content, workout challenges, home workouts, gym workouts, healthy food menus, and others. This also includes the results of story reposts by Nadia Ninette's followers through one of Instagram's features, namely Instagram Stories, where her followers tag her account, @nadianinette. Keywords: Personal branding, influencer, Instagram, content